Changes in Resources and Volunteering: A Longitudinal Study of Active Engagement Among Older Europeans - Hämäläinen, Hans; Tanskanen, Antti O.; Arpino, Bruno; Abuladze, Liili; Solé-Auró, Aïda; Danielsbacka, Mirkka (Oxford University Press (OUP), 2025)
Background and Objectives
Volunteering is an important dimension of successful aging. Although prior studies have found that personal resources such as health and financial situations are associated with volunteering, there is a lack of research exploring the relationship between resource changes and volunteering. Here, we investigated whether changes in individuals’ resources were associated with volunteer engagement among older Europeans.
Research Design and Methods
Using data from the Survey of Health, Aging, and Retirement in Europe, collected in five waves between 2011 and 2020 across 19 countries (57,410 observations from 17,498 individuals aged 50 and above), we employed asymmetric fixed-effect ordinal regression models to investigate whether positive or negative resource changes were associated with the frequency of volunteering over time. We used three resource indicators: health, financial condition, and time availability (measured by engagement in paid work, grandparenting, and family care).
Results
Health deterioration and worsening financial condition were associated with a decreased frequency of volunteering. A transition out of weekly paid work and beginning to provide weekly grandchild care were both associated with an increased frequency of volunteering. We did not detect any further significant effects of resource changes on volunteering.
Discussion and Implications
Our study revealed asymmetrical associations between changes in resources and volunteering, providing new insights into their interplay. The results deepen our understanding of successful aging by emphasizing the need to consider the dynamics of all resources that either facilitate or hinder active engagements among older adults.